The Native English-Speaker Teacher’s (NEST’s) Technique In Teaching Speaking At MAN Sooko Mojokerto (RETAIN, 2013)
This study investigated the technique that was used by NEST English-Speaker Teacher (NEST) in teaching speaking. It sought the answer to the following questions: What is the technique that is used by the NEST in teaching English speaking? What are students’ opinions about NEST’s technique in teaching English speaking? What are the students’ attitudes towards the NEST’s technique? What does the Non-NEST learn from the NEST’s technique? This study was limited to one NEST and in one class which NEST would teach speaking skill to the students. So, qualitative case study was the research method. The data were taken from the results of fieldnotes, semi-structured interview, and questionnaire. The data were analyzed qualitatively. It was found that when NEST taught at the class XI-IPA1 at MAN Sooko Mojokerto, NEST used 1-minute speech as the technique. In this technique, the students were asked to make a story based on their own experience. Before giving speech about 1 minute in front of the class, the students were asked to make an otline based on what they were going to talk. Almost all of the students felt more motivated because the technique that was used by NEST was enjoyable and not boring. The students’ attitudes towards the technique were also positive. They listened and followed seriously. From the technique that was used, non-NEST could learn lot of things, such as the strategy in learning, the way on how to make the students more motivated to learn English, and the enthusiasm of NEST in preparing all of it. Key words: Native English-Speaker Teacher (NEST), technique, teaching speaking Abstrak Penelitian ini menginvestigasi jenis technique mengajar yang digunakan oleh NEST English-Speaker Teacher (NEST) dalam teaching speaking. Ini mencari jawaban dari pertanyaan: Apa technique yang digunakan oleh NEST dalam mengajar speaking? Apa pendapat siswa tentang technique yang digunakan oleh NEST? Bagaimana sikap siswa terhadap technique yang digunakan oleh NEST? Apa saja yang bisa dipelajari oleh non-NEST dari NEST? Penelitian ini dibatasi pada satu guru NEST dan pada satu kelas saja yang akan diajar speaking oleh NEST. Jadi qualitative case study adalah metode penelitiannya. Data diambil dari hasil fieldnotes, interview semi-structured, dan questionnaire. Data dianalisa secara kualitatif. Ditemukan bahwa saat mengajar di kelas XI IPA1 MAN Sooko Mojokerto, NEST menggunakan technique 1-minute speech. Dalam technique tersebut, siswa diminta untuk membuat cerita tentang pengalamannya sendiri. Sebelum memberikan speech sekitar 1 menit di depan kelas, siswa diminta untuk membuat outline tentang apa yang akan dibicarakan. Hampir seluruh siswa merasa lebih termotivasi karena technique yang digunakan oleh NEST menyenangkan dan tidak membosankan. Sikap siswa terhadap technique tersebut juga sangat positif. Mereka mendengarkan dan mengikuti dengan seksama. Dari technique yang telah digunakan, non NEST bisa mempelajari banyak hal, sperti strategi dalam pembelajaran, cara untuk membuat siswa lebih termotivasi dalam belajar bahasa Inggris, dan antusiasme NEST dalam mempersiapkan semuanya. Kata Kunci: Guru asli bahasa Inggris, teknik, mengajar berbicara